Modern Love : Romance, Intimacy, and the Marriage Crisis. - Shumway, David (NYU Press, 2003)
"My ideas of romance came from the movies," said Woody Allen, and it is to the movies--as well as to novels, advice columns, and self-help books--that David Shumway turns for his history of modern love. Modern Love argues that a crisis in the meaning and experience of marriage emerged when it lost its institutional function of controlling the distribution of property, and instead came to be seen as a locus for feelings of desire, togetherness, and loss. Over the course of the twentieth century, partly in response to this crisis, a new language of love--"intimacy"--Emerged, not so much replacing bu.